Forest seedling community response to understorey filtering by tree ferns. (19th September 2018) - Brock, James M. R.; Perry, George L. W.; Burkhardt, Tynan; Burns, Bruce R.
Abstract: Questions: Large pteridophytes frequently co‐occur with conifers and angiosperms in the understorey of temperate broad‐leaved podocarp forests but interactions between them are poorly understood. We evaluated the impact of tree ferns on the regeneration niche of vascular woody species to determine whether tree ferns function as biotic filters and influence seedling occurrence. We asked the following questions: (i) do understorey tree ferns influence the woody seedling bank, and (ii) which potential mechanisms drive any such influence? Location: Auckland and Waikato regions, northern New Zealand. Methods: We measured woody seedlings in 164 1‐m 2 plots in northern New Zealand temperate broad‐leaved podocarp forest and used multivariate analyses and modelling to assess the relative contributions of abiotic and biotic effects on community composition and seedling abundance. We manipulated the environments beneath 160 tree fern individuals by removing fronds and/or macro‐litter in a balanced factorial design, and recorded the response of the seedling community over 1 year. We then assessed the relative influences of shading and litter depth on the seedling community response. Results: Distance to the nearest tree fern was the best predictor of understorey seedling abundance; seedling abundance decreased beneath tree ferns. There was no strong evidence, however, that tree ferns influence seedling community composition; although the palm Rhopalostylis sapida, was consistently present away from tree fern micro‐sites. Removal of tree fern shading and macro‐litter both influenced the local seedling community; conifers responded positively, and most consistently to frond removal. Frond‐shading and deep litter reduced seedling species richness and seedling abundance. Conclusions: Tree ferns influence the woody seedling bank in temperate broad‐leaved podocarp forest through increased shading and macro‐litter accumulation, both of which reduce the abundance of angiosperm and conifer seedlings. A tree fern‐dominated understorey is likely to reduce conifer establishment and may limit direct competition among woody plants by reducing densities and regeneration opportunities immediately beneath tree fern canopies. Abstract : This study comprises observational and experimental elements discerning the biotic effect of tree ferns on forest seedling regeneration in mixed angiosperm–conifer forests of northern New Zealand. We accounted for dispersal limitations, environmental variation and within‐side heterogeneity in 160 experimental plots and identified tree ferns as a biotic filter reducing gymnosperm seedling abundance and frequency through shading.